The Use of Distributed Learning to Support Students with Dyslexia at the University of East London - Wright, E.; Hughes, G. (Proceedings of the International Conference on Networked Learning, 2002)
The poster display will illustrate the problems to be dealt with in setting up and monitoring a discussion forum for dyslexic students at the University of East London using the ‘Discussions’ facility within WebCT. The aim is to encourage self-help and peer support, and to create a distributed community of dyslexic learners within the virtual learning environment. Issues covered are the design and layout of the site, the involvement and training of the dyslexia support tutor team, initial student log-in and continuing use, the level of support and monitoring required and the evaluation of WebCT as a suitable medium for the forum.